2019
DOI: 10.1002/hbm.24852
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal‐movement and ventral‐form regions are functionally connected during visual‐speech recognition

Abstract: Faces convey social information such as emotion and speech. Facial emotion processing is supported via interactions between dorsal-movement and ventral-form visual cortex regions. Here, we explored, for the first time, whether similar dorsalventral interactions (assessed via functional connectivity), might also exist for visualspeech processing. We then examined whether altered dorsal-ventral connectivity is observed in adults with high-functioning autism spectrum disorder (ASD), a disorder associated with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 142 publications
(276 reference statements)
1
6
0
Order By: Relevance
“…For the FFA ROI, the localiser was thresholded with a cluster size of 25 voxels. This cluster size is similar to previous reports for the FFA using this design and contrast (Borowiak et al, 2019;von Kriegstein et al, 2008). We did not observe responses in an analogous region in the left hemisphere at a threshold of <0.01 uncorrected.…”
Section: Regions Of Interestsupporting
confidence: 92%
See 3 more Smart Citations
“…For the FFA ROI, the localiser was thresholded with a cluster size of 25 voxels. This cluster size is similar to previous reports for the FFA using this design and contrast (Borowiak et al, 2019;von Kriegstein et al, 2008). We did not observe responses in an analogous region in the left hemisphere at a threshold of <0.01 uncorrected.…”
Section: Regions Of Interestsupporting
confidence: 92%
“…We used a functional localiser (Borowiak, Maguinness, & von Kriegstein, 2019 ; design as von Kriegstein et al, 2008 ) to establish the location of the face‐sensitive FFA and the pSTS‐mFA within participants. The face stimuli consisted of still frames, extracted using Final Cut Pro software (Apple Inc., CA), from video sequences of 50 identities (25 female; 19–34 years).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that dynamic face processing in ASD is disrupted from early visual processing (i.e., V1-MTG). One recent study [128] provided evidence that individuals with ASD may have difficulties in face-to-face communication. Participants performed visual speech recognition tasks by matching an articulated syllable with a target syllable while watching a silent video of speakers articulating a syllable.…”
Section: Dynamic Face Processingmentioning
confidence: 99%